2017
DOI: 10.1080/20961790.2017.1334353
|View full text |Cite
|
Sign up to set email alerts
|

CT-scan vs. 3D surface scanning of a skull: first considerations regarding reproducibility issues

Abstract: Three-dimensional surface scanning (3DSS) and multi-detector computed tomography (MDCT) are two techniques that are used in legal medicine for digitalizing objects, a body or body parts such as bones. While these techniques are more and more commonly employed, surprisingly little information is known about the quality rendering of digitalized three-dimensional (3D) models provided by each of them. This paper presents findings related to the measurement precision of 3D models obtained through observation of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Centre universitaire romand de médecine légale, Lausanne-Genève, CURML) manages important amounts of forensic cases in Switzerland. A pioneer in the development of forensic imaging [ 7 ], CT and 3D surface scans are routinely performed at the CURML, and a series of projects on the use of CT and 3D surface scanning models in anthropology are ongoing [ 8 , 9 ]. In the research presented here, 3D models were created using both a CT scanner and a 3D surface scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Centre universitaire romand de médecine légale, Lausanne-Genève, CURML) manages important amounts of forensic cases in Switzerland. A pioneer in the development of forensic imaging [ 7 ], CT and 3D surface scans are routinely performed at the CURML, and a series of projects on the use of CT and 3D surface scanning models in anthropology are ongoing [ 8 , 9 ]. In the research presented here, 3D models were created using both a CT scanner and a 3D surface scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Second, 3D scanner allows the user to work with real 3D files, which we cannot obtain from other reported twodimensional techniques. 9,18 It may be argued that we could have either measured the femoral angles on digital photography images of femur specimens or calculated them directly onto the bones.…”
Section: Discussionmentioning
confidence: 99%
“…The aim was to increase the visualisation of the femoral cortices, decreasing the radiotransparency of the bone and thus improving the quality of the femoral captures. Secondly, 3D scanner allows the user to work with real 3D files, which the authors cannot obtain from other reported 2D techniques 9 18 . It may be argued that the authors could have either measured the femoral angles on digital photography images of femur specimens or calculated them directly onto the bones.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional crime scene and forensic reconstruction and documentation methods are now giving way to three-dimensional (3D) imaging [ [10] , [11] , [12] , [13] ]. Methods include X-ray computed tomography (including micro-CT) [ 14 , 15 ], laser scanning [ 15 , 16 ], structured-light scanning [ 16 ], and 3D photogrammetry [ 9 , 17 ]. A number of researchers have emphasized the clear advantages to 3D digitization over other recording techniques i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have emphasized the clear advantages to 3D digitization over other recording techniques i.e. examination of fragile and otherwise inaccessible material, the production of affordable, high-quality replicas for display, teaching, and research, increased accuracy and enhanced data sharing [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , 17 , 18 ]. The use of surface scanning in forensic anthropology and medicine has been well established [ 19 ], in contexts such as the analysis of burned remains [ 20 ], replication of anthropological specimens for curation and illustration [ 20 ], recording taphonomic changes [ 21 ], evaluating trauma [ 1 , 22 ], determining bullet pathways [ 23 ], and presenting evidence in court [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%